TEXTUAL-COMPARATIVE STUDY OF COPIES AND PREAMBLE PART OF THE WORK " QISASI RABGUZI " (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article contains information about the copies of the work "Qisasi Rabguzi" written by Nasiruddin Rabguzi and the textual-comparative study of the preface of the work. The article also describes the reasons for writing the work, its components and the experiences of the period.